PERSEPSI MASYARAKAT DAN DAMPAK SISTEM ZONASI UNTUK PEMERATAAN AKSES SEKOLAH JENJANG SEKOLAH DASAR DI KECAMATAN SERENGAN KOTA SURAKARTA - Wahdan Najib Habiby; Saroh Nur Fiatun (Universitas Muhammadiyah Surakarta, 2019)
The purpose of this study is to describe: 1) the implementation of school zoning in Serengan Subdistrict, Surakarta City; 2) public perception of the school zoning system of Serengan Sub-District, Surakarta City; and 3) the impact of the zoning system in Serengan Subdistrict, Surakarta City. This type of research is descriptive qualitative research. The qualitative data analysis technique uses the concepts conveyed by Miles and Huberman. Data collection techniques carried out through questionnaires, interviews, and documentation. The results showed: 1) the implementation of the zoning system in Serengan Sub-district in Surakarta was in accordance with the Technical Guidelines for Implementing Acceptance of New Students in Surakarta City, but to fulfill the quota of study groups was opened offline registration paths 2) The results of the public perception questionnaire on the zoning system for equal distribution of school access in schools Serengan Subdistrict, Surakarta City for the understanding of the zoning system in the latest PPDB, which is classified as being medium for a positive response value of 47%. However, the negative response value and the doubtful response value are in the category of less, 30% and 23%. Whereas public perception for indicators of zoning system implementation included a high 67% positive response and 14% and 19% less response. 3) The results of the questionnaire perception of the public about the impact of the zoning system, the impact felt by the community is high, with a positive response of 68%. Doubtful responses and negative responses included less namely 17% and 14%.